Alexithymia in relation to alcohol expectancies in alcohol-dependent outpatients - Thorberg, F.; Young, R.; Lyvers, M.; Sullivan, K.; Hasking, Penelope; London, E.; Tyssen, R.; Connor, J.; Feeney, G. (2016)
© 2016 Elsevier Ireland Ltd. Alexithymia and alcohol outcome expectancies were investigated in 355 alcohol-dependent treatment seekers. Patients with alexithymia gave stronger self-report ratings of expectancies of affective change related to beliefs that alcohol leads to negative mood states and assertion, that alcohol enhances social skills, compared to those without alexithymia. The findings suggest that alcohol-dependent outpatients with alexithymia may drink to experience intensified negative emotions and improved social functioning.